(untitled) - Menon, Shailaja (Laxmi Nagar, Delhi, 2003)
Contents of material: Introduction. Cyber intrusion. Impact of cyber crimes and problems in investigation. Protection of intellectual property in cyberspace. Laws governing cyber piracy in India and the international treaties.
Keywords: Cyberterrorism,Internet,Intellectual property,Computer crimes